Estratégias para inserção das televisões universitárias no ecossistema da TV 3.0: da Web ao DTV+ - Chaves, Miguel Bruno Alves; Rocha, Luciana Rodrigues; Sousa, Li-Chang Shuen; Moreno, Marcelo Ferreira (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This position paper presents preliminary findings from an ongoing master’s research project that investigates the challenges and opportunities for integrating Brazilian university television stations into the Digital TV 3.0 ecosystem. The analysis begins with a classification of the 190 university TV stations registered with the Brazilian Association of University Televisions (ABTU), based on their distribution models. It then proposes a typology of editorial profiles specifically for stations operating via over-the-air broadcast. As a case study, the research examines university television stations located in São Luís, Maranhão, to identify concrete technical, institutional, and regulatory barriers to their integration into the DTV+ environment. Building on these findings, the paper outlines a two-phase roadmap: first, to expand the presence of university TV stations on RNP’s Eduplay platform; and second, to advance toward a dedicated application for connected TVs and DTV+ receivers.